PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) MENGGUNAKAN LKS BERBASIS MULTIREPRESENTASITERHADAP HASIL BELAJAR FISIKA - Suyati; Kamaluddin; Ali , Muhammad (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to determine the effect of the Children Learning In Science (CLIS) learning model using Multi-representation-based worksheets on Physics Learning Outcomes. This type of research was a quasi-experimental design with a non-equivalent pretest-posttest group design. The population of this study were all students of class X SMAN 5 Palu. The sampling technique used in this study was purposive sampling with the research sample were class X MIA 5 as the experimental group and class X MIA 4 as the control group. The physics learning outcome instrument was in the form of a multiple-choice test that has been validated by an expert validator. The physics learning outcomes test obtained showed that the average pretest score of the experimental group was 11.17 and the control group was 9.37 while the average posttest score of the experimental group was 19.23 and the control group was 16.77. Hypothesis test The t-test shows that there are differences in the two classes. Based on the results of the N-Gain test, the two classes are each in the category, namely the experimental class was in the medium category with an N-Gain value of 42.45% and the control class was in the middle category. while the N-Gain value is 41.77%. Thus, it can be concluded that there is an influence of the Children Learning In Science (CLIS) learning model on the learning outcomes of class X students of SMA Negeri 5 Palu.